THE MECHANISM OF THE LIFE CYCLE OF THE CONSUMER GOODS INDUSTRY SECTOR OF INDOMIE PRODUCTS AT PT.INDOFOOD SUKSES MAKMUR TBK. - Rico Nur Ilham; Amelia; Cut Zahrani; Indah Fadhillah; Ratri Pangestika (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Indonesia has extraordinary wealth in terms of resources, both natural and cultural resources. One form of this heritage can be seen in the culinary field, including food inherited from ancestors and food acculturated by foreign cultures. An example is noodles or bakmi, which were introduced by the Chinese community as popular food in Indonesia. For the Chinese people, noodles have a shape like a string that can be stretched out long, and the way to eat them by sucking them up illustrates the durability of life. On the other hand, instant noodles or noodles that can be served quickly are industrial in a broad and narrow sense vizIn a broad sense, industry is all activities that humans take advantage of natural resources while in the narrow sense industry is an activity an economy that processes raw materials into semi-finished materials. Investment is spending at this time to buy real assets (such as land, houses, cars and so on) or financial assets with the aim of obtaining greater income in the future. A well-managed product life cycle will help marketers better able to retain profitable products and drop unprofitable products. Sandals are the initial stage in the product life cycle where manufacturers introduce new products to the market or society in general. This stage is characterized by slow growth where the product is introduced to become well known and begins to be accepted by customers. This period saw an increase in sales. This maturity stage can be divided into 3 stages. The first is the slow scaling stage, in which total sales increase but most of the demand comes from existing customers and few new buyers. Second, the stability stage, where sales volume does not increase anymore but remains constant because only old customers buy the product. No more new buyers coming in. Third, gradual decline, where sales decline because some customers start switching to other products. In the decline phase, sales and profits will experience a significant decrease. If you don't apply the right strategy, products that offer risk disappear from the market. the life cycle is the life cycle from birth to death. Understanding the life cycle can also be interpreted as a series of changes and growth in the development of an organism from the beginning of life to maturity and produce offspring.